Fournier Gangrene in A 65 Years Old Obese Female with Uncontrolled Type II Diabetes Mellitus - A Case Report - Coffee, Rochella Krismurning; Setiawan, Kelvin; Rosadi, Bramastha Aires; Lawanto, Terry Renata (JBN (Jurnal Bedah Nasional); Vol 4 No 1 (2020): JBN (Jurnal Bedah Nasional)DO - 10.24843/JBN.2020.v04.i01.p01, 2020)
Background : Fournier gangrene is a disease with characteristic of rapidly progressive necrotizing fasciitis in the perianal and genitourinary area. Case: Usually it affects men, but we hereby present Fournier gangrene in an obese, diabetic, middle-aged woman. Her chief complaint was discomfort, swelling and foul odor coming from her genital area. Thus, she was diagnosed with Fournier gangrene and underwent emergency surgical debridement with local anaesthesia. After removing all necrotic tissues, overlying pus and debris, wounds were left open until granulation were seen and optimal condition of the tissue and planned for reconstructive surgery and additional debridement if needed. Local wound dressings were done with silver dressings and washed with 0.1% Polyaminopropyl biguanide solution. Patient received oral antibiotics daily for five days and visit surgery polyclinic twice a week for wound toilet and observation of wound condition. Conclusion: Early diagnosis, administration of broad-spectrum antibiotics and emergency debridement is important factors to successful outcome of Fournier gangrene.